Application of autologous cortical bone grafts for femoral non‐union fractures in two dogs. Issue 1 (20th February 2020) - Muroi, Norihiro; Kanno, Nobuo; Suzuki, Shuji; Harada, Yasuji; Hara, Yasushi
Abstract : Two dogs with non‐union fractures and osteomyelitis in the femoral diaphysis were referred to the authors' hospital. During surgery, the defects were reconstructed using autologous cortical bones harvested from the contralateral femoral diaphysis. Graft fixation was performed by a double‐plate technique in both cases. Autogenous cancellous bone was also grafted between the host bone and the graft in both cases. Antibiotics were administered for two to three weeks. In cases 1 and 2, no loosening of the implant or lameness was observed after 31 months and 10 months, respectively. Autologous cortical bone grafts are useful in reconstructing large‐sized bone defects of the femoral diaphysis associated with non‐union fracture and osteomyelitis.